2016
DOI: 10.3400/avd.oa.16-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Glycyrrhizin Infusion for the Prevention of Venous Thrombosis on the Tissue Expression of Antithrombin in a Rat Model

Abstract: Objective: Using a thrombus model prepared by ligation of the inferior vena cava (IVC), the influences of the glycoside, glycyrrhizin, on plasma antithrombin levels and antithrombin mRNA expression levels in the liver and IVC with the inhibition of venous thrombosis were investigated. Materials and Methods: The rat IVC was exposed and ligated for 24 h immediately after the intravenous administration of 300 mg/kg glycyrrhizin. Among antithrombotic drugs, the Xa inhibitor, fondaparinux sodium, was used as a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(18 reference statements)
0
2
0
1
Order By: Relevance
“…It can inhibit platelet aggregation caused by thrombin activation in rats ( Mendes-Silva et al, 2003 ). Pretreatment with GL (300 mg/kg) can reduce the average thrombus weight and anti-thrombin gene transcription levels in the liver as well as the inferior vena cava in rats ( Nakata and Kira, 2016 ). The mechanism of how GL affects thrombin remains unclear, and additional studies are necessary.…”
Section: Resultsmentioning
confidence: 99%
“…It can inhibit platelet aggregation caused by thrombin activation in rats ( Mendes-Silva et al, 2003 ). Pretreatment with GL (300 mg/kg) can reduce the average thrombus weight and anti-thrombin gene transcription levels in the liver as well as the inferior vena cava in rats ( Nakata and Kira, 2016 ). The mechanism of how GL affects thrombin remains unclear, and additional studies are necessary.…”
Section: Resultsmentioning
confidence: 99%
“…Os animais foram anestesiados (ketamina 75mg/kg e xilazina 10mg/kg) via intraperitoneal (Nakata & Kira, 2016). Em seguida o animal foi posicionado em uma mesa cirúrgica, realizada uma laparotomia mediana, os órgãos expostos foram mantidos hidratados com soro fisiológico 0,9% e isolada delicadamente a região da VCI.…”
Section: Metodologiaunclassified
“…Glycyrrhizin was observed to have an antithrombotic effect in two models of inducing thrombosis in rats ( Mendes-Silva et al, 2003 ). Glycyrrhizin administration preoperative could prevent venous thrombosis during the initial phase of thrombus formation by inhibition of neutrophil adhesion to venous endothelium ( Nakata et al, 2008 ; Nakata and Kira, 2016 ). In a recent report, Shin and his colleagues observed that licorice root at large doses could induce intracranial hemorrhagic stroke and cerebral microbleeds due to direct inhibitors of blood coagulation factor Xa as well as of thrombin by glycyrrhizin and glycyrrhetinic acid ( Shin et al, 2019 ).…”
Section: The Potential Therapeutic Effect Of Glycyrrhizin and Licoricmentioning
confidence: 99%